Reverberation impairs brainstem temporal representations of voiced vowel sounds: challenging “periodicity-tagged” segregation of competing speech in rooms - Sayles, Mark; Stasiak, Arkadiusz; Winter, Ian M. (Frontiers in Systems Neuroscience, 2015)
The auditory system typically processes information from concurrently active sound sources (e.g., two voices speaking at once), in the presence of multiple delayed, attenuated and distorted sound-wave reflections (reverberation). Brainstem circuits help segregate these complex acoustic mixtures into “auditory objects”. Psychophysical studies demonstrate a strong interaction between reverberation and fundamental-frequency (F0) modulation, leading to impaired segregation of competing vowels when segregation is on the basis of F0 differences. Neurophysiological studies of complex-sound segregation have concentrated on sounds with steady F0s, in anechoic environments. However, F0 modulation and reverberation are quasi-ubiquitous. We examine the ability of 129 single units in the ventral cochlear nucleus of the anesthetized guinea pig to segregate the concurrent synthetic vowel sounds /a/ and /i/, based on temporal discharge patterns under closed-field conditions. We address the effects of added real-room reverberation, F0 modulation, and the interaction of these two factors, on brainstem neural segregation of voiced speech sounds. A firing-rate representation of single-vowels’ spectral envelopes is robust to the combination of F0 modulation and reverberation: local firing-rate maxima and minima across the tonotopic array code vowel-formant structure. However, single-vowel F0-related periodicity information in shuffled inter-spike interval distributions is significantly degraded in the combined presence of reverberation and F0 modulation. Hence, segregation of double-vowels’ spectral energy into two streams (corresponding to the two vowels), on the basis of temporal discharge patterns, is impaired by reverberation; specifically when F0 is modulated. All unit types (primary-like, chopper, onset) are similarly affected. These results offer neurophysiological insights to perceptual organization of complex acoustic scenes under realistically challenging listening conditions.